Cost Analysis of Inpatient Stroke Treatment at Panembahan Senopati Bantul Regional General Hospital Based on INA-CBG's tariff in 2023 - Hadning, Ingenida; Mouretha, Vrizca; Viviandhari, Daniek; Kusumaningtyas, Triana Arum (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Stroke in Yogyakarta has the second highest prevalence rate in Indonesia, which requires long-term care and rehabilitation at a high cost. Stroke patients treated in classes 1, 2 and 3 are known to have experienced an increase in INA-CBG rates based on Minister of Health Regulation Number 3 of 2023. However, some hospitals often experience discrepancies between actual costs and INA-CBG's rates. Therefore, this study is the first to assess the cost of inpatient stroke treatment using the INA-CBG's tariff based on the Minister of Health Regulation Number 3 of 2023. This study aims to determine the average actual cost, the appropriateness of the average actual cost, and the difference in actual costs at a Regional General Hospital according to the INA-CBG's tariff in 2023. The research method used an observational design with a cross-sectional approach and retrospective data collection on stroke patients hospitalized from January to September 2023. Data were analyzed using the descriptive analysis method and one sample t-test if the data were normally distributed and the Wilcoxon test if the data were not normally distributed. Based on the study's results, it is known that the average actual cost does not exceed the INA-CBG tariff, so the hospital is profitable.